2020
DOI: 10.3390/foods9070885
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of the Larvae of the Alien Invasive Wasp Vespa velutina nigrithorax and Amino Acid Composition of the Larval Saliva

Abstract: The systematic investigations on the value of social wasps as a food resource are deficient, in spite of the long history of the utilization of social wasps as food and pharmaceutical bioresources. Vespa velutina nigrithorax is an invasive alien wasp species that is currently dominating in East Asia and Europe, bringing huge economic damages. As a control over alien species is made when the valuable utilization of the invasive species as a potential resource are discovered, investigations on the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
2
12
1
1
Order By: Relevance
“…The amino acid distributions seen in our study are in general agreement with a previously published report, although the contents of some of the amino acids in the current study were a little less than what was reported earlier [1]. The total amino acid content as protein content of Vespa broods is comparable with other reports on edible insects, including wasps (V. velutina nigrithorax: 48.64 [30], V. mandarinia: 59.7 [2], V. basalis: 43.91, V. mandarinia: 52.20, V. velutina auraria: 49.03, V. tropica ducalis: 42.44 [1]). In the earlier study, as with ours, overall glutamic acid was the most abundant amino acid.…”
Section: Amino Acid Compositionsupporting
confidence: 92%
“…The amino acid distributions seen in our study are in general agreement with a previously published report, although the contents of some of the amino acids in the current study were a little less than what was reported earlier [1]. The total amino acid content as protein content of Vespa broods is comparable with other reports on edible insects, including wasps (V. velutina nigrithorax: 48.64 [30], V. mandarinia: 59.7 [2], V. basalis: 43.91, V. mandarinia: 52.20, V. velutina auraria: 49.03, V. tropica ducalis: 42.44 [1]). In the earlier study, as with ours, overall glutamic acid was the most abundant amino acid.…”
Section: Amino Acid Compositionsupporting
confidence: 92%
“…Jeong et al [ 46 ] point out that despite their long history of utilization as food and pharmaceutical bioresources, the value of social wasps as a food resource is poorly appreciated and researched. Especially, not only are the larvae of the invasive Vespa velutina nigrithorax rich in nutrition and safe to eat but their saliva’s amino acid composition has been shown to be worthy of further study in the context of amino acid supplementation and exercise enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…After the first workers emerge, they will take over the responsibilities step-by-step and the queen will become sedentary, her only function will be laying eggs. The adults feed mostly on sweet fluids, like nectar or fruit pulps, but the larvae are carnivorous, so queen and later mainly workers hunt to feed their offspring (Jeong et al 2020). Unlike the European hornet, the oriental hornets are maximum active in the hottest time of the day, because their pigments can adsorb the sun beams and transform it in their own energy (Galushko et al 2005).…”
Section: Introductionmentioning
confidence: 99%